2020
DOI: 10.1503/cjs.010218
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon attitudes toward point of care ultrasound for biliary disease: a nationwide Canadian survey

Abstract: Surgeon attitudes toward point of care ultrasound for biliary disease: a nationwide Canadian survey G allstone disease affects more than 20 million Americans yearly. 1 In Ontario, 260 elective cholecystectomies per 100 000 patients are performed each year. 2 Point of care ultrasound (PoCUS) has a growing role in the diagnosis of gallstone disease. 3 Results of PoCUS are similarly accurate compared with formal radiology-performed ultrasounds. 4 Emergency physicians who use biliary PoCUS improve emergency depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…About half (48.9%, 65/120) felt that the sensitivity of POCUS was less than 50%. 9 Understanding the accuracy of POCUS will help determine whether it is a modality that can enhance diagnostic accuracy obtained from clinical and radiologist-based assessments. Our study was designed to evaluate the accuracy of ED POCUS, using gold standard diagnostic techniques such as a formal ultrasound, abdominal CT scan, and final diagnosis obtained from surgical and pathology findings.…”
Section: Introductionmentioning
confidence: 99%
“…About half (48.9%, 65/120) felt that the sensitivity of POCUS was less than 50%. 9 Understanding the accuracy of POCUS will help determine whether it is a modality that can enhance diagnostic accuracy obtained from clinical and radiologist-based assessments. Our study was designed to evaluate the accuracy of ED POCUS, using gold standard diagnostic techniques such as a formal ultrasound, abdominal CT scan, and final diagnosis obtained from surgical and pathology findings.…”
Section: Introductionmentioning
confidence: 99%
“…28,31 A recent 2020 survey evaluating Canadian general surgeons' perceptions of a biliary Bedside US revealed that most surgeons believed the sensitivity of Bedside US to be much lower for cholelithiasis and cholecystitis than actual literature results. 49 Results from a similar study mirrored the lack of confidence by general surgery and other consultants on trusting Bedside US performed by emergency medicine physicians. 50 Meanwhile, there remains a paucity of studies in which the Bedside US was the sole modality of imaging for diagnosing biliary disease resulting in operative management.…”
Section: Discussionmentioning
confidence: 75%
“…Lack of confidence in the accuracy of POCUS and its ability to provide the requisite information seems to be chief among these concerns, despite the literature demonstrating that POCUS is reliable. 13 In jurisdictions such as the USA, concerns over medicolegal risk and/or financial incentives may be a barrier to adoption of POCUS for surgical decision-making. The research presented in this article suggests that the subspecialty of the surgeon managing the patient may have an influence.…”
Section: Discussionmentioning
confidence: 99%
“… 12 A recent Canadian national survey showed that 60% of practicing surgeons had a total lack of confidence in ED POCUS for the diagnosis of biliary disease. 13 This lack of confidence leads many surgeons to seek confirmatory radiology department imaging prior to operating on the gallbladder. The unanswered question is whether this additional step of obtaining a RUS adds value for the surgeon over the information available by POCUS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation